Social Behavior of Captive Black-Tailed Prairie Dogs (Mammalia, Rodentia) with Changing Numbers of Observers - Eltorai, A.E.M.; Sussman, R.W. (Вестник зоологии, 2011)
Black-tailed prairie dogs Cynomys ludovicianus (Ord, 1815) are diurnal rodents that live in intricate cities. Their social complexity rivals that of some primates, and, in some respects, resembles the behavior of humans. Due to the rich variety of readily-observable, sophisticated behaviors such as coloniality, infanticide, anti-predator behaviors, “kin recognition”, cooperation, conflict, and reproductive success, the black-tailed prairie dog is a wonderful model species for the study of behavior. Using a captive population, we were able to quantify the effects of observation on key social behaviors.